Pediatric Exercise Testing: Value and Implications of Peak Oxygen Uptake - Paolo T. Pianosi (Children, 2017)
Peak oxygen uptake (peak V ˙ O 2 ) measured by clinical exercise testing is the benchmark for aerobic fitness. Aerobic fitness, estimated from maximal treadmill exercise, is a predictor of mortality in adults. Peak V ˙ O 2 was shown to predict longevity in patients aged 7–35 years with cystic fibrosis over 25 years ago. A surge of exercise studies in young adults with congenital heart disease over the past decade has revealed significant prognostic information. Three years ago, the first clinical trial in children with pulmonary arterial hypertension used peak V ˙ O 2 as an endpoint that likewise delivered clinically relevant data. Cardiopulmonary exercise testing provides clinicians with biomarkers and clinical outcomes, and researchers with novel insights into fundamental biological mechanisms reflecting an integrated physiological response hidden at rest. Momentum from these pioneering observations in multiple disease states should impel clinicians to employ similar methods in other patient populations; e.g., sickle cell disease. Advances in pediatric exercise science will elucidate new pathways that may identify novel biomarkers. Our initial aim of this essay is to highlight the clinical relevance of exercise testing to determine peak V ˙ O 2 , and thereby convince clinicians of its merit, stimulating future clinical investigators to broaden the application of exercise testing in pediatrics.